Phylogeographical analysis reveals multiple conservation units in brook lampreys Lampetra planeri of portuguese streams - Pereira, Ana Martins (2010)
The populations of brook lamprey Lampetra planeri of Portuguese Rivers were analysed phylogeographically using a fragment of 644 bp of the mitochondrial control region of 158 individuals from six populations. Samples representing L. planeri and migratory lampreys Lampetra fluviatilis of rivers draining to the North Sea and the Baltic Sea were also included to assess the relationships of Portuguese samples. The data support a clear differentiation of all the populations studied. Several populations, which are isolated among themselves and also from the migratory lampreys, proved to be entirely composed of private haplotypes, a finding that supports some time of independent evolutionary history for these populations. This, combined with the geographic confinement to small water bodies, justifies the recognition of at least four conservation units in the Portuguese rivers Sado, São Pedro, Nabão and Inha.